COMING INTO BEING AN EMPATHIC DOCTOR: MODERN VIEWS AND CHALLENGES - I.A. Kolisnyk; A.I. Pankevych; A.M. Hohol (Український стоматологічний альманах)
Medical reformation process based on a human-centered approach requires universities to train healthcare professionals who are able to update knowledge and skills quickly, to adapt to new conditions, and be highly qualified and competitive specialists. The development of qualities that ensure communication with patients such as empathy is still of great importance.